Diversity of arbuscular mycorrhizal fungi in Tectona grandis Linn.f. plantations and their effects on growth of micropropagated plantlets - Amornrat Chaiyasen (2018)
© 2017, Springer Science+Business Media Dordrecht. Regeneration of stands of valuable tropical hardwood tree species for sustainable harvest requires production of seedlings with high probabilities of survival. One way to enhance the vigor of plants for outplanting is pre-colonization of roots by arbuscular mycorrhizal (AM) fungi. We pursued the strategy that the most promising AM fungus candidates for inoculation would be those associated with the tree of interest in the field. AM fungus communities were assessed in five plantations of Tectona grandis Linn.f. A total of 18 AM fungal morphotypes were found, representing four families: Glomeraceae (49.6%), Acaulosporaceae (24.9%), Claroideoglomeraceae (20.8%), and Gigasporaceae (4.8%). AM fungus spore density was negatively correlated with soil organic carbon. Some of these AM fungi, plus Rhizophagus irregularis, were established in pot culture and in vitro with transformed carrot roots, and subsequently used to inoculate micropropagated plantlets of T. grandis. Tectona grandis plantlets inoculated in vitro were successfully colonized by all AM fungi studied. Plants inoculated with Funneliformis mosseae were taller than uninoculated plants. Tectona grandis plantlets inoculated with the AM fungus Claroideoglomus etunicatum PBT03 were taller than uninoculated controls in ex vitro experiments. This study provides early insight for the targeted use of the AM symbiosis in production of important tree species in future greenhouse studies and reforestation.